The Current Features of Pyelonephritis Etiological Structure in Children - T.V. Yaroshevskaya; O.S. Koreniuk; V.A. Minakova; O.V. Medvedskaya (Zaslavsky O.Yu., 2016)
Background. The seriousness of the prognosis, diagnostic and treatment difficulties determine the relevance of the problem of pyelonephritis, and the practitioner should know current regional data on the age structure of uropathogens. Analysis of these data provides a basis for correction of empirical and causal treatment of the disease. The aim of research: to study the isolation rate and the structure of uropathogens in children with acute and chronic pyelonephritis depending on the age, disease activity and the nature of comorbidity. Materials and methods. Medical cases histories were analyzed in 239 children discharged in 2013-2015 from the nephrology department of Municipal Institution «Municipal Children's Clinical Hospital № 2 of Dnipropetrovsk Regional Council», with a diagnosis of acute or chronic pyelonephritis. We conducted urine culture followed by the identification of the causative agent and determination of its sensitivity to antibiotics. Uropathogens spectra have been examined depending on the age, gender, urodynamic disorders, concomitant diseases of the digestive system, the presence of infection foci in nasopharynx. Results. Sterility urine test showed that opportunistic pathogenic microflora was detected in 100 out of 239 children. Inoculation of microorganisms from the urine in this study reached 41.8 %. E.coli was detected in 43 of 100 children, E.faecalis - in 34, K.pneumoniae - in 8, Proteus - in 6, S.aureus - in 4, P.aeruginosa - in 3, S.haemolyticus - in 2. Microbial associations were detected in 2 children, there were E.coli and Enterococcus. When talking about the age aspect, a tendency to relative increase of Proteus (14.3 %) and Pseudomonas aeruginosa (28.5 %) incidence in infants draws attention. In boys, the ratio of E.coli and Enterococcus was 16.7 and 56.7 %, respectively, that was different from that of girls - 54.3 and 24.3 %, respectively. It was noted that early children's age, the activity of pyelonephritis, the presence of obstructive pyelonephritis were associated with an increase of the proportion of E.coli, Pseudomonas aeruginosa and Proteus. In case of dysmetabolic nephropathy, intestinal dysbiosis, the presence of infection foci in nasopharynx, the change in the uropathogens spectrum took place in favor of Enterococcus, the relative frequency of S.aureus increased. The sensitivity of the selected pathogens to antibiotics was determined that allows to identify features of antibacterial therapy of pyelonephritis in children. The high sensitivity of E.coli to ceftriaxone, amoxiclav, and Enterococcus faecalis - to vancomycin, ampicillin, furaginum and fosfomicin was discovered. Conclusions. According to the results of the research, microbial inoculation from the urine in children with pyelonephritis is 41.8 %. Leading uropathogens in pediatric pyelonephritis are E.coli (43 %) and E.faecalis (34 %). The spectrum of opportunistic microorganisms derived from urine differed depending on the age, sex, comorbidity that should be considered when selecting empiric therapy.